Interval-valued intuitionistic fuzzy cognitive maps for supplier selection - Hájek, Petr; Procházka, Ondřej (Springer Science and Business Media, 2018)
Fuzzy cognitive maps (FCMs) are used to aid decision-making in complex highly nonlinear problems dealing with uncertainty. In FCMs, decision concepts are linked in order to represent causal relationships. In business decision-making, it is difficult to precisely estimate the strengths of the relationships. To address this issue, we propose interval-valued intuitionistic FCMs (IVIFCMs). A multi-criteria decision making method is introduced in which the concepts of IVIFCM represent criteria and the edges represent interaction effects among the criteria. To identify the best alternative, the steady state solution of the IVIFCM is compared with the desired values of the concepts. The proposed method provides us with an effective tool for multi-attribute decision making in complex decision-making problems with a strong uncertainty.
Intervalově ohodnocené intuicionistické fuzzy kognitivní mapy pro výběr dodavatele
Keywords: Fuzzy cognitive map; Interval-valued intuitionistic fuzzy sets; Supplier selection; Multi-criteria decision making; Fuzzy kognitivní mapa; Intervalově ohodnocené intuitionistické fuzzy množiny; Výběr dodavatele; Vícekriteriální rozhodování